2002
DOI: 10.1034/j.1601-5223.2002.1360304.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of durable powdery mildew resistance in a common wheat line

Abstract: Genetic studies using monosomic and hybridological analyses had confirmed that resistance of a common wheat line k‐15560 to powdery mildew in seedling stage was conditioned by one dominant gene located on chromosome 7B, and resistance in adult stage was controlled by two dominant genes. Cytological analysis of meiosis in the F1 monosomic hybrids has revealed reciprocal translocation involving chromosomes 2A/7A. In the F1 monosomic hybrids genes, causing a decrease in pairing were found on chromosomes 3B and 4D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…On the other hand, the resistance in the crosses 72 x Atilla-12 and 72 x Basribey was regulated by one dominant and one recessive gene, and two dominant genes in the cross 72 x Golia (Table 5). In accordance with our results, Peusha et al (2002) suggested that resistance at the adult stage in wheat cultivars was controlled by two independent dominant genes and Griffey and Das (1994) estimated the number of genes controlling adult plant resistance in the wheat cultivars Knox and Massey to be two to three. Besides, Srnic (2003) reported that in greenhouse studies powdery mildew resistance in four germplasm x germplasm populations segregated as a digenic trait.…”
Section: Resultssupporting
confidence: 71%
“…On the other hand, the resistance in the crosses 72 x Atilla-12 and 72 x Basribey was regulated by one dominant and one recessive gene, and two dominant genes in the cross 72 x Golia (Table 5). In accordance with our results, Peusha et al (2002) suggested that resistance at the adult stage in wheat cultivars was controlled by two independent dominant genes and Griffey and Das (1994) estimated the number of genes controlling adult plant resistance in the wheat cultivars Knox and Massey to be two to three. Besides, Srnic (2003) reported that in greenhouse studies powdery mildew resistance in four germplasm x germplasm populations segregated as a digenic trait.…”
Section: Resultssupporting
confidence: 71%
“…Screening of old wheat cultivars, landraces and related species for resistance to powdery mildew started in the 1930's (Hsam and Zeller, 2002) and Pm genes have since been identified in many different, widely distributed wheat cultivars and landraces. Non-major gene resistance has been sought such as the durable adult plant resistance found in the landrace accession k-15560 (Peusha et al, 2002).…”
Section: Powdery Mildewmentioning
confidence: 99%
“…Genetic studies confirmed that cultivar 'Amigo', has Pm17 and leaf rust resistance gene Lr24 on a translocated chromosome involving 1 A and 1B, respectively (Hsam and Zeller, 2006), the Pm8/ Pm1 alleles at the locus (Mohler et al, 2008) and Amigo is a source of Sr24/Lr24 (The et al,1991). There are many explanations for the number of genes that conditioned resistance to powdery mildew in wheat (Peusha et al, 2002, Srnic, 2003Ilker et al, 2009). Adult plant resistance (APR) to cereal fungal diseases provide protection in a crop's post-seedling stages typically between tillering and booting according to Adult Plant Resistance Fact Sheets GRDC, Nov. (2012).…”
Section: Introductionmentioning
confidence: 96%